Simulated effect of tobacco tax variation on population health in California. - Kaplan, R M (2001)
OBJECTIVES: This study simulated the effects of tobacco excise tax increases on population health. METHODS: Five simulations were used to estimate health outcomes associated with tobacco tax policies: (1) the effects of price on smoking prevalence; (2) the effects of tobacco use on years of potential life lost; (3) the effect of tobacco use on quality of life (morbidity); (4) the integration of prevalence, mortality, and morbidity into a model of quality adjusted life years (QALYs); and (5) the development of confidence intervals around these estimates. Effects were estimated for 1 year after the tax's initiation and 75 years into the future. RESULTS: In California, a $0.50 tax increase and price elasticity of -0.40 would result in about 8389 QALYs (95% confidence interval [CI] = 4629, 12,113) saved the first year. Greater benefits would accrue each year until a steady state was reached after 75 years, when 52,136 QALYs (95% CI = 38,297, 66,262) would accrue each year. Higher taxes would produce even greater health benefits. CONCLUSIONS: A tobacco excise tax may be among a few policy options that will enhance a population's health status while making revenues available to government.